Importance of documentation in nursing practice - Amajla Topuz; Ivana Miljković (Биомедицинска истраживања, 2020)
Nursing is an established discipline that helps people in having a productive and healthy life as well as in coping with health problems in the best possible way using established skills. The application of nursing interventions and measures based on the analysis and assessment of patient needs, problems and difficulties observed, and his or her abilities as well as on a continuous assessment and verification of the results obtained is carried out by means of the healthcare process. The rational and logical basis for defining and solving patient's problems is within the scope of healthcare process. Professional networking as well as the networking of all hierarchical structures is a priority where the filing of nursing documentation in a centralized information system is concerned. Nursing documentation is used to establish effective communication between non-medical and medical staff, between nurses and, between families, as well as to establish effective communication with the healthcare system during the overall patient care process.
Keywords: nursing documentation; established skills; deficiencies; nurse; health care